EPIDEMIOLOGICAL ANALYSIS OF COVID-19 CASES IN GORONTALO CITY (CASE STUDY OF KOTA TENGAH SUBDISTRICT) - Lia Amalia; Yasir Mokodompis (International Journal of Health Science & Medical Research, 2023)
Coronavirus Disease or COVID-19, is still a concern around the world. COVID-19 is a new disease that was previously unknown before it finally appeared in Wuhan, China, in December 2019. A new strain of coronavirus causes COVID-19, The Novel Coronavirus 2019 (2019-nCoV), and is officially named Severe Acute Respiratory Syndrome-Coronavirus 2 (SARS-CoV- 2). The novelty of this study is to analyze the epidemiology of Covid-19 cases in Gorontalo City. The purpose of this study is to analyze the epidemiology of Covid 19 disease in Gorontalo City. The type of research used is an observational survey with a descriptive approach. The population and samples are all covid 19 patients in 2020 – 2022 who live in the Puskesmas Kota Tengah area, Kota Tengah Subdistrict, Gorontalo City. The sampling technique is Purposive Sampling. The results showed the highest prevalence of covid 19 in 2021 was 2.3%, the frequency distribution of covid 19 sufferers by the highest sex in 2021 was 344 people (55.6%), the frequency distribution based on the age group of covid 19 sufferers was highest in 2022 age group 25-29 years as many as 25 people (23.6%), frequency distribution based on the month of the highest incidence in 2022 February as many as 67 people (63.2%),  frequency distribution based on the highest residence in 2020 residences in Pulubala Village were 76 people (25.0%) and the highest CFR in 2021 was 3.6%. The Conclusion is the prevalence of covid-19 in 2020 was 1.1%, there was an increase in covid-19 cases in 2021 to 2.3%, and there was a decrease in mid-2022 with a prevalence of 0.4%.Keywords: Covid-19; Epidemiology; People; Place; Time.